2018
DOI: 10.1111/pai.13005
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of susceptibility to air quality and weather in individual children with atopic dermatitis

Abstract: Background Exposure to air pollution aggravates symptoms of atopic dermatitis (AD) in children in the population studies. Variability in individual patient's response from individual susceptibility is needed to be explored. Objective This study aimed to investigate spectrum of individual variability in the associations between AD symptoms and air quality. Methods We enrolled 89 children aged 0‐6 years with AD (22 890 person‐days). Daily manifestation of symptoms was recorded for an average of 257 days (range 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…A recently published review observed that NO 2 exposure could play a role in the development of childhood atopic dermatitis (Hendricks et al 2019). A panel study conducted in Seoul found that children with atopic dermatitis (33.7%) were sensitive to NO 2 concentrations (Noh et al 2019). To a larger extent, our result was consistent with those studies.…”
Section: Discussionsupporting
confidence: 91%
“…A recently published review observed that NO 2 exposure could play a role in the development of childhood atopic dermatitis (Hendricks et al 2019). A panel study conducted in Seoul found that children with atopic dermatitis (33.7%) were sensitive to NO 2 concentrations (Noh et al 2019). To a larger extent, our result was consistent with those studies.…”
Section: Discussionsupporting
confidence: 91%
“…However, with an odds ratio of 1.05 and the small quantity of observational, cohort studies, and individual studies, the statistical power of this meta-analysis is limited. Several new studies have been published that were not included in this meta-analysis [54][55][56][57][58][59][60]. More recently, Krämer and co-workers have reviewed this evidence by combining data from 57 environmental epidemiological studies in a systematic review [61].…”
Section: Epidemiologymentioning
confidence: 99%
“…Inflammatory dermatoses are sensitive to changing environmental conditions; air pollutants, such as small particulate matter, may exacerbate chronic conditions like pemphigus and atopic dermatitis (discussed in this issue’s section on pediatric dermatology as the focus of Schachtel, Dyer, and Boos (Ed: add ref to article in this issue).). ( Kim et al, 2017 ); ( Koohgoli et al, 2017 ); ( Li et al, 2016 ); ( Nguyen et al, 2019 ); ( Noh et al, 2019 ); ( Ren et al, 2019 ); ( Rosenbach, 2019 ) In turn, these air particles are tied to climate change both causally (released via fossil fuel burning) and as a result of expanded pollen seasons,( Ziska et al, 2011 ) wildfire activity,( Spracklen et al, 2000 ) and urban air stagnation events that trap pollutants in the lower atmosphere. ( Trail et al, 2013 ) Returning to skin cancer, air pollutants have also been shown to potentiate oxidative damage to the skin.…”
Section: Overview Of the Dermatologic Impacts Of Climate Changementioning
confidence: 99%